Risk factors for in vitro fertilization failures in women with adenomyosis-associated infertility - Mekan R. Orazov; Liudmila M. Mikhaleva; Viktor E. Radzinskiy; Marina B. Khamoshina; Abecha K. Barinova; Dmitry G. Aryutin; Marina V. Tsaregorodtseva; Irina V. Besman; Vafa Yu. Ibragimova (IP Berlin A.V., 2023)
Aim. To identify risk factors for in vitro fertilization (IVF) failures in women with adenomyosis-associated infertility. Materials and methods. The study included 83 patients of reproductive age with adenomyosis. Women were divided into two groups: the main group (n=53) included patients with adenomyosis and a history of 1 or more unsuccessful attempts at embryo transfer, and the comparison group (n=30) included women with adenomyosis without impaired fertile function. The mean age of the patients was 364.0 years. Results. Gynecological conditions such as cervical dysplasia, noninflammatory vaginal diseases, and a history of sexually transmitted infections (STIs) were significantly (5-fold) more common in patients with a history of IVF failures (p0.05). A high prevalence of endocrine and digestive system disorders (27.7 and 7.7 times, respectively) was found in infertile women with adenomyosis (p0.05). Coagulation disorders were identified 4.8 times more often in women with adenomyosis-associated infertility and IVF failures. Inflammatory and proliferative endometrial diseases (hyperplasia, intrauterine synechia, and chronic endometritis) were significantly more common in patients in the main group than in patients with adenomyosis without impaired fertility (p0.05). Conclusion. Risk factors for IVF failure in women with adenomyosis-associated infertility are other specified coagulation defects [D68.8] (antiphospholipid syndrome), odds ratio (OR) 4.8, 95% confidence interval (CI) 1.120.9; dysplasia of cervix uteri, unspecified [N87.9] (OR 10.2, 95% CI 1.292.4), other noninflammatory disorders of vagina [N89.7] (OR 10.2, 95% CI 1.292.4), STIs (OR 12.7, 95% CI 1.4112.5), endocrine system disorders (OR 27.7, 95% CI 1.5516.5), and digestive system disorders (OR 7.8, 95% CI 2.227.8).